2014
DOI: 10.1007/s40477-014-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasonography in the management of patients with primary hyperparathyroidism: retrospective comparison with technetium-99m sestamibi scintigraphy

Abstract: Objective Primary hyperparathyroidism (PHPT) is a common endocrine disorder that can be cured only by parathyroidectomy. Cervical ultrasonography and scintigraphy are the imaging studies most widely used for preoperative localization of the affected glands. The aim of this retrospective comparative study was to define the respective roles of ultrasonography and parathyroid scintigraphy in these cases. Materials and methods We analyzed 108 patients who had undergone parathyroidectomies for PHPT following cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 33 publications
0
32
0
5
Order By: Relevance
“…These can also occur in cases of thyroid nodules or concomitant Hashimoto's thyroiditis. The sensitivity of US technique is strongly dependent on the operator's experience, being about 84% when performed by an experienced doctor (7). Advantages of the US technique include low cost, wide availability, absence of ionizing radiation exposure, together with the possibility of evaluating concomitant thyroid disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…These can also occur in cases of thyroid nodules or concomitant Hashimoto's thyroiditis. The sensitivity of US technique is strongly dependent on the operator's experience, being about 84% when performed by an experienced doctor (7). Advantages of the US technique include low cost, wide availability, absence of ionizing radiation exposure, together with the possibility of evaluating concomitant thyroid disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, both modalities lack detail regarding surrounding anatomy, and sonography is highly operator-dependent. [5][6][7] In the past decade, multiphase CT has emerged as an additional technique for adenoma localization. 1,2,[8][9][10][11][12][13][14] In addition to lesion identification, CT allows precise localization based on welldefined anatomic landmarks.…”
mentioning
confidence: 99%
“…However, the sensitivity of ultrasonography fluctuates between 22% and 80%, because it is user dependent and limited in its ability to localize retroesophageal, retrotracheal, retrosternal, intrathyroidal, mediastinal, small, and deep cervical glands [41,48,49]. Vitetta et al found that sonography performed by an expert was associated with an appreciably superior diagnostic yield than 99mTc sestamibi [50]. Thus, ultrasound can be used as the main method for preoperative localization of pathological parathyroid tissues [50].…”
Section: Differential Diagnosis and Work-upmentioning
confidence: 99%
“…Vitetta et al found that sonography performed by an expert was associated with an appreciably superior diagnostic yield than 99mTc sestamibi [50]. Thus, ultrasound can be used as the main method for preoperative localization of pathological parathyroid tissues [50].…”
Section: Differential Diagnosis and Work-upmentioning
confidence: 99%